2014
DOI: 10.1007/s11192-014-1264-0
|View full text |Cite
|
Sign up to set email alerts
|

How well developed are altmetrics? A cross-disciplinary analysis of the presence of ‘alternative metrics’ in scientific publications

Abstract: In this paper an analysis of the presence and possibilities of altmetrics for bibliometric and performance analysis is carried out. Using the web based tool Impact Story, we collected metrics for 20,000 random publications from the Web of Science. We studied both the presence and distribution of altmetrics in the set of publications, across fields, document types and over publication years, as well as the extent to which altmetrics correlate with citation indicators. The main result of the study is that the al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
264
3
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(308 citation statements)
references
References 44 publications
26
264
3
5
Order By: Relevance
“…All the aforementioned studies, among others, have shown that altmetrics (and more particularly downloads) are in correlation with citation statistics. For instance, Zahedi, Costas and Wouters (2014) found a moderate Spearman correlation between Mendely readership counts and citation indicators in their study entitled 'How well developed are altmetrics? A cross-disciplinary analysis of the presence of "alternative metrics" in scientific publications'.…”
Section: Discussionmentioning
confidence: 99%
“…All the aforementioned studies, among others, have shown that altmetrics (and more particularly downloads) are in correlation with citation statistics. For instance, Zahedi, Costas and Wouters (2014) found a moderate Spearman correlation between Mendely readership counts and citation indicators in their study entitled 'How well developed are altmetrics? A cross-disciplinary analysis of the presence of "alternative metrics" in scientific publications'.…”
Section: Discussionmentioning
confidence: 99%
“…A more finegrained alternative is to exploit a faster-growing source of impact evidence from the web for article-level indicators (Priem, Taraborelli, Groth, & Neylon, 2011; or both options can be combined: Haustein & Siebenlist, 2011). Of the various alternative indicators (altmetrics) that have been proposed, Mendeley reader counts are the most promising for early impact evidence because of their relatively high correlations with citation counts and early appearance (Zahedi, Costas, & Wouters, 2014). Although tweets may appear sooner, they are much less reliable for impact indicators (Haustein, Larivière, Thelwall, Amyot, & Peters, 2014;Thelwall, Haustein, Larivière, & Sugimoto, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies investigated the correlation between altmetrics and downloads/ citations claimed positive correlations but relatively weak, thus supporting the idea that altmetrics do not reflect the same concept of impact as citations (105,108,109,(111)(112)(113)(114). Peters (109), Bar-Ilan (113) and Xuemei (114) found the Mendeley as the most powerful tool for articles sampling.…”
Section: Resultsmentioning
confidence: 78%